Les composantes de l'amenagement forestier et leurs incidences financieres - Bertrand, A.; Babin, D.; Nasi, Robert (1999)
The various factors common to forest management schemes are examined : sustained output, biodiversity conservation, and multiple uses. These factors are combined in different ways from case to case. Consideration of them in the management process includes specific kinds of financial impact for each factor. The diverse range of management situations must therefore lead to properly adapted financial set-ups. The planned generalization of the implementation of forest management schemes will involve introducing economies of scale and reducing unit management costs. This represents a tremendous challenge for research. Likewise, the generalization of management schemes will entail a basic redefinition of the duties of forest administration agents